2019
DOI: 10.21608/jades.2019.68501
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of the use of brackish ground water in integrated aqua-agriculture systems

Abstract: Water scarcity is a great challenge and a growing problem for all countries. The present researchfocuses on the rational utilization of water resources with different quality through studying the effects of different parameters on water use efficiency and productivity, the investigation used different parameters such as water resources, sowing dates and water shortage on the amount of water applied, water use efficiency, yieldand net return of barley, in a semi-arid region during growing season 2014-2015. A Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…IAAS operates on a principle of wastewater reuse where aquaculture effluents are utilized as both irrigation water and nutrient sources for plants (Farrag et al 2021 ; Sewilam et al 2022 ). Previous studies have shown significant improvements in crop yield as well as crop water and nutrient use efficiency in plants cultivated under IAAS (Dey et al 2010 ; Mariscal-Lagarda et al 2012 ; M.Moursy et al 2019 ; Farrag et al 2021 ; Sewilam et al 2022 ). Likewise, several studies have also shown improved water quality, survival, and growth performance of fish reared under IAAS (Mariscal-Lagarda et al 2012 ; Farrag et al 2021 ; Sewilam et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…IAAS operates on a principle of wastewater reuse where aquaculture effluents are utilized as both irrigation water and nutrient sources for plants (Farrag et al 2021 ; Sewilam et al 2022 ). Previous studies have shown significant improvements in crop yield as well as crop water and nutrient use efficiency in plants cultivated under IAAS (Dey et al 2010 ; Mariscal-Lagarda et al 2012 ; M.Moursy et al 2019 ; Farrag et al 2021 ; Sewilam et al 2022 ). Likewise, several studies have also shown improved water quality, survival, and growth performance of fish reared under IAAS (Mariscal-Lagarda et al 2012 ; Farrag et al 2021 ; Sewilam et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%